1993
DOI: 10.1016/0167-4838(93)90262-p
|View full text |Cite
|
Sign up to set email alerts
|

Identity and some properties of the l-threonine aldolase activity manifested by pure 2-amino-3-ketobutyrate ligase of Escherichia coli

Abstract: 2-Amino-3-ketobutyrate ligase catalyzes the reversible, pyridoxal 5'-phosphate-dependent condensation of glycine with acetyl CoA forming the unstable intermediate, 2-amino-3-ketobutyrate. Several independent lines of evidence indicate that the pure protein obtained in the purification of this ligase from Escherichia coli also has L-threonine aldolase activity. The evidence includes: (a), a constant ratio of specific activities (aldolase/ligase) at all stages of purifying 2-amino-3-ketobutyrate ligase to homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Second, Thr can be produced via a pathway involving steps catalyzed by 2-amino-3-ketobutyrate ligase and threonine dehydrogenase [44], with 13 C-labeled sodium acetate serving as a source of acetyl-CoA (Figure 1). However, the production of large quantities of Thr is likely to be compromised because (i) the intermediate 2-amino-3-ketobutyrate has a half-life estimated to be less than 1 minute [45] or 10 minutes [46] at pH 7, with spontaneous decarboxylation diverting a large fraction of the isotopically labeled material into aminoacetone [44] and (ii) 2-amino-3-ketobutyrate ligase also possesses some threonine aldolase activity [47] which would destroy the desired product (Thr) in a coupled enzymatic reaction. A third approach is also suggested in Figure 1, starting from 2-ketobutyrate (2KB, 13 CH 3 12 CD 2 COCOONa), a well-established and inexpensive commercially available precursor for labeling of Ile δ1 positions with 1 H and 13 C [11].…”
Section: Resultsmentioning
confidence: 99%
“…Second, Thr can be produced via a pathway involving steps catalyzed by 2-amino-3-ketobutyrate ligase and threonine dehydrogenase [44], with 13 C-labeled sodium acetate serving as a source of acetyl-CoA (Figure 1). However, the production of large quantities of Thr is likely to be compromised because (i) the intermediate 2-amino-3-ketobutyrate has a half-life estimated to be less than 1 minute [45] or 10 minutes [46] at pH 7, with spontaneous decarboxylation diverting a large fraction of the isotopically labeled material into aminoacetone [44] and (ii) 2-amino-3-ketobutyrate ligase also possesses some threonine aldolase activity [47] which would destroy the desired product (Thr) in a coupled enzymatic reaction. A third approach is also suggested in Figure 1, starting from 2-ketobutyrate (2KB, 13 CH 3 12 CD 2 COCOONa), a well-established and inexpensive commercially available precursor for labeling of Ile δ1 positions with 1 H and 13 C [11].…”
Section: Resultsmentioning
confidence: 99%
“…Pronounced aminoacetone oxidase activity was detected for LAAO, although it was first identified as an amino acid oxidase [11]. Cellular aminoacetone can be derived either from threonine or a condensation of glycine and acetyl-CoA [24], [27]. Threonine dehydrogenase, a key enzyme in L-threonine metabolism, catalyzes the conversion of L-threonine to 2-amino-3-ketobutyrate, and the latter is spontaneously decarboxylated to aminoacetone [28].…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme also acts on both l ‐threonine and l ‐ allo ‐threonine (unpublished results). Marcus and Dekker showed that a homogeneous 2‐amino‐3‐ketobutyrate ligase of E. coli show low activity toward these threonine isomers [13], but the present enzyme, LATA, does not cleave l ‐threonine. To the best of our knowledge, the present reports demonstrates the first instance of the l ‐ allo ‐threonine specific enzyme, LATA, which exhibits neither l ‐threonine aldolase nor SHMT activity.…”
Section: Discussionmentioning
confidence: 69%